2008
DOI: 10.1002/path.2462
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive clinicopathological associations of amplification of the cortactin gene at 11q13 in head and neck squamous cell carcinomas

Abstract: Amplification of the 11q13 region is a prevalent genetic alteration in head and neck squamous cell carcinoma (HNSCC). We investigated the clinical significance of cortactin (CTTN) and cyclin D1 (CCND1) amplification in both malignant transformation and tumour progression. CTTN and CCND1 amplification was analysed by differential and real-time PCR in a prospective series of laryngeal/pharyngeal carcinomas and archival premalignant tissues. CTTN mRNA and protein expression were respectively determined by real-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
89
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 26 publications
9
89
0
Order By: Relevance
“…Cortactin is an oncoprotein located on chromosome 11q13 along with cyclin D1, a site that is frequently amplified in HNSCC (44). In accordance with our findings, high tumor CTTN expression has been shown to correlate with increased aggressiveness and poor outcome in many cancers, but most frequently in HNSCC (37,45).…”
Section: Fig 5 Model For Radioresistance Mediated By Cortactin In Hsupporting
confidence: 89%
“…Cortactin is an oncoprotein located on chromosome 11q13 along with cyclin D1, a site that is frequently amplified in HNSCC (44). In accordance with our findings, high tumor CTTN expression has been shown to correlate with increased aggressiveness and poor outcome in many cancers, but most frequently in HNSCC (37,45).…”
Section: Fig 5 Model For Radioresistance Mediated By Cortactin In Hsupporting
confidence: 89%
“…Discussion 11q13 is a frequently amplified chromosomal region in several human cancers with poor prognosis (3-7). Although CCND1 is considered to be the main tumor-promoting gene in this amplicon, it does not have predictive value for the survival of HNSCC and breast cancer patients (8,(11)(12)(13)(14). The 11q13 amplicon harbors several independent amplification cores, indicating the presence of additional driving oncogenes in this region (6,15,16,34).…”
Section: Ano1 Regulates Egfr-and Calcium-dependent Signaling Pathwaysmentioning
confidence: 99%
“…Although cyclin D1 (CCND1) has been considered to be the main driver of the 11q13 amplicon (8)(9)(10), it is not sufficient for malignant transformation of normal breast cells and lacks predictive value for the survival of head-and-neck squamous cell carcinoma (HNSCC) or breast cancer patients (8,(11)(12)(13)(14). Instead, the region has been shown to harbor several independent amplification cores, indicating that other genes could be potential driving oncogenes (6,15,16).…”
mentioning
confidence: 99%
“…An increase of motility and invasiveness was described for HNSCC cell lines with CTTN amplification and cortactin overexpression, which decreased after selective cortactin knock-down (22). Retrospective studies found an association of amplification and adverse patient outcome in HNSCC (23). In this respect, the increase of transcriptional activity on chromosomal bands 3q26.3-qter and 11q12-q13 detected by CESH in our analysis is probably the result of distinct DNA copy number gains in these chromosome regions underlining the validity and reliability of the present experimental approach.…”
Section: Discussionmentioning
confidence: 99%